Plant Responses Underlying Timely Specialized Metabolites Induction of Brassica Crops - Doghri, Maroua; Rodríguez, Víctor Manuel; Kliebenstein, Daniel J.; Francisco, Marta (Frontiers in Plant Science, 2022)
Large subset of plant stress-signaling pathways, including those related with chemical defenses production, exhibits diurnal or circadian oscillations. However, to what extent the dimension of time and/or the circadian clock contribute to the accumulation of plant specialized metabolites under stress responses remain largely unknown. Because it has been hypothesized that plant responses to physical stress is a mechanism common to mounting a response against a broad range of environmental stresses, including herbivory, we have utilized mechanical wounding as the stress stimulus to determine the direct contribution of time of day on the induced defenses of Brassica crops. We analyzed glucosinolates (GSLs) from leaves of broccoli (Brassica oleracea) and turnip greens (Brassica rapa) following exposure to mechanical wounding at dawn (ZT0), mid-day (ZT4) and dusk (ZT8). Several of these compounds were differentially accumulated, and changes were dependent upon the time of day at wounding was performed. This response this response varied considerably between species. In a parallel experiment, we investigated whether cyclical activation of Brassica phytochemicals in response to wounding might prime plants against herbivore attack. Results evidenced that maximal responsiveness of plant chemical defense against larvae of the generalist pest Mamestra brassicae could be occurring at ZT0 in broccoli and ZT8 in turnip greens. We further tested for global trends of timely induced compounds involved in herbivore resistance. Metabolome analysis indicated that sulphur-containing phytochemicals, GSL hydrolysis products, auxin-signaling components, and other metabolites activators of plant disease resistance (nicotinamide and pipecolate) had important contributions to the responses of M. brassicae feeding behavior in broccoli at morning. Overall, the findings in this study highlight a significant role for time of day in the wounding stress responsive metabolome, which is in turn affecting plant-herbivore interactions.